Gaea-Tima the gigantis. Vol. 02 - KENT (Manga artist) (Kodansha USA Publishing, 2025)
A gigantic monster returns to the town it ravaged years earlier in this poignant kaiju manga from the creator of the hit series Colorless. In the spirit of the classic Godzilla and Godzilla Minus One, GAEA-TIMA combines thunderous action and character drama with the social conscience and thematic complexity of the genre's post-war roots. A monster that people call GAEA-TIMA devastates a small, seaside town. Ten years later, the resilient community has emerged as a tourist destination, and Miyako, who became a local celebrity by surviving the attack, is making a living selling mini-replicas of the beast. But when GAEA-TIMA returns, Miyako and her neighbors will discover that their enduring connection to the creature goes deeper than tourism and trauma. Just what is the true agenda behind the attack of the "gigantis?" Are there more like GAEA-TIMA waiting for their moment? And is humanity capable of responding to violence with anything other than more violence?